KEGIATAN PEMELIHARAAN JALAN DESA TERAPU TAHUN 2022 - Muhammad Fahmi; Mohdari; Syafril; Neti Rosiana Fadilah; Wiszda Asma; Lidiana; Yuliani (Jurnal Abdimas Sosek (Jurnal Pengabdian dan Pemberdayaan Masyarakat Sosial Ekonomi), 2023)
Infrastructure development is a must for a nation that wants to progress because it can increase the acceleration of the traffic of people and goods. Infrastructure development does not only occur in urban areas but also has to reach rural areas which are sources of production of several public consumption goods such as agricultural and plantation products. The government has established a village fund program as a driving force for development in rural areas with a large enough budget so that villages continue to grow and attract young people to return home to build their villages. One sector that is of concern to village officials is road access in rural areas which is still not good. We aim to serve this community to help Terapu Village, Aluh-aluh District, Banjar Regency, South Kalimantan Province in using village funds for the construction of road facilities in the village. This service has a good impact on the village community because it gets input and opinions in the use of village funds for the benefit of the community.